A student and staff partnership in the development of a student directed independent learning toolkit - Draper, Michael; Fisher, Danielle (International Journal for Students as Partners, 2020)
This case study offers reflection and evaluation on a student and staff partnership that utilises the principles of action research in the development of a practical toolkit to support directed independent learning by students. Since 2016, in an ongoing project under the auspices of the Hillary Rodham Clinton School of Law internship scheme, students have worked in partnership with members of staff to address the support for students’ development of independent learning skills to enable their full engagement with different university teaching styles. This project theme was chosen because it has the potential to have a significant impact on creating or supporting student confidence in students’ academic ability and associated mental wellbeing and sense of satisfaction and achievement. Students are best placed to provide solutions and inform the development of independent learning skills within a student-staff partnership project that facilitates active collaboration and the power to co-create.